Village Fund Allocation for Community Welfare in Hatunuru Village, East Taniwel District, West Seram Regency - Nussy, Dessy Natallia; Leuwol, Ferdinand Salomo; Lasaiba, Mohammad Amin (Jurnal Pendidikan Geografi Unpatti, 2023)
Regional and village development, which are part of national development, aim to increase local government's capacity to provide services to the community and increase regional capabilities in managing economic resources efficiently for regional progress and community welfare. This study aims to determine the Allocation of Village Funds for Community Welfare in Hatunuru Village, East Taniwel District, West Seram Regency. This research method uses a descriptive qualitative method. Based on the results of the study, it can be concluded that the management of village fund finances can meet the level of satisfaction. For the sake of community welfare, the selection of village officials is carried out very selectively. The success of development in Hatunuru Village is very good, where every local community feels the impact and benefits of allocating village funds, and at least the community feels fair in allocating village funds.